Google Apps. - Conner, Nancy, 1961- (Missing manual., 2009)
"From the same people who brought you Google Apps: The Missing Manual comes this collection of video tutorials to guide you through the key features of Google Apps. Covering topics from how to set up a basic spreadsheet in Google Docs to managing all the users in your domain, each video is designed to be a quick guide to get you up and running in minutes"--Resource description page (viewed April 6, 2010).